Characterization of mucosal cytokine profile in ulcerative colitis patients under conventional and anti-TNF-a treatment. Issue 12 (December 2020) - Lopetuso, Loris Riccardo; Corbi, Maddalena; Scaldaferri, Franco; Petito, Valentina; Graziani, Cristina; Castri, Federica; Neri, Matteo; Gasbarrini, Antonio; Sgambato, Alessandro; Papa, Alfredo
Abstract : Objectives: Cytokines play a pivotal role in inflammatory bowel disease (IBD). We investigated the expression of inflammatory and regulatory cytokines in inflamed and uninflamed mucosal samples of ulcerative colitis patients. Methods: Twenty-five ulcerative colitis patients were enrolled. Bioptic samples from inflamed and not inflamed intestinal areas were obtained. Multiplex analysis for inflammatory and regulatory cytokines was performed. Serum C-reactive protein (CRP) was assessed. Endoscopic Mayo score and histological simplified Geboes score were calculated. Results: Interleukin (IL)-1Ra, IL-6, IL-8, IL-17, induced Protein (IP)-10, monocyte chemoattractant protein (MCP)-1, macrophage inflammatory protein (MIP)-1a, MIP-1b resulted increased in ulcerative colitis inflamed vs ulcerative colitis not inflamed areas. No differences were registered between conventional and anti-tumor necrosis factor-a regimens. No difference with CRP levels was found. IL-7 resulted reduced in patients with endoscopic Mayo score ≥2. All the not inflamed samples had a Geboes score <2A, while all the inflamed specimens had a Geboes score ≥2B. IL-1Ra resulted increased in the group with a Geboes score ≥4. Conclusions: Inflamed and adjacent not inflamed mucosal areas in ulcerative colitis patients share detailed inflammatory molecular pathways, but can be differentiated endoscopically and histologically on the basis of specific cytokines levels. This underlines the complexity of the mucosal cytokine network in ulcerative colitis and highlights the major limitations of a single proinflammatory target therapeutic strategy in IBD.